KERUGIAN INDONESIA DALAM KERJASAMA INDONESIA JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) - Paskalia Sabtaliani Sandori (Jurusan Ilmu Hubungan Internasional, 2016)
At the outset there has been optimism that Indonesia-Japan Economic Partnership Agreement (IJEPA) will benefit both countries. IJEPA is bilateral economic cooperation between Indonesia and Japan based on three pillars; Market access liberalisation, trade and investment facilitation, and capacity building cooperation. After several years, Indonesia found the disadvantage of this bilateral scheme. This paper aims at explaining why the IJEPA disfavour to Indonesia’s export towards Japan. It finds that the Japan’s standardisation hinders Indonesia’s Export, while at the same time, the IJEPA kick up Japan’s export to Indonesia, mainly electronic and automotive. This paper suggests that Indonesia should take a serious review to the IJEPA scheme.